Acute myocardial infarction in a previously healthy child: case report - Catarina Almeida; Marisa Pereira; Sofia Granja; João C. Silva; Jorge Moreira (Publicaciones Permanyer, 2024)
Introduction: Acute myocardial infarction is a rare life-threatening event in children. Although more frequent in those with congenital heart disease and/or abnormal coronary anatomy, it can occur in otherwise healthy children. Case report: We present the case of a previously healthy seven-year-old boy evaluated because of chest pain. An ECG revealed major repolarization abnormalities in the inferior and left precordial leads and an echocardiogram showed mild global left ventriclar dysfunction and a dyskinetic apical interventricular septum. Laboratory testing showed an isolated, but significant, elevation of cardiac markers. He underwent cardiac catheterization that confirmed an occlusion of the distal segment of the left descending artery. Cardiovascular magnetic resonance findings indicated a recent transmural infarction of the apical septal segment. Discussion: Despite being an uncommon entity in the pediatric population, myocardial ischemia and infarction can be the reason behind plain chest pain. The diagnosis warrants a high index of suspicion and should prompt meticulous cardiac testing.